Botulinum toxin in the management of chronic migraine: clinical evidence and experience. (February 2017) - Escher, Claus M; Paracka, Lejla; Dressler, Dirk; Kollewe, Katja
Chronic migraine (CM) is a severely disabling neurological condition characterized by episodes of pulsating unilateral or bilateral headache. The United States Food and Drug Administration (FDA) approved onabotulinumtoxinA (Botox ® ) for the prophylactic treatment of CM in 2010. It has been shown that onabotulinumtoxinA is effective in the reduction of headache frequency and severity in patients with CM. Treatment is well tolerated by the patients. This review reports on the history of botulinum neurotoxin (BoNT) in CM and presents the current clinical evidence for the use of onabotulinumtoxinA in the treatment of CM.